Evaluation of Tremor-Assisted Eating Devices: A Comparative Study of Usability and Patient Preference in Essential Tremor - Adabi, Kian; Ondo, William (Movement disorders clinical practice (Hoboken, N.J.), 2025)
A number of adaptive devices are marketed and sold to patients with tremor; however, there is essentially no published data on their efficacy. The aim of the study was to evaluate the objective efficacy and subjective preferences of 6 commercially available adaptive eating devices for patients with tremor. We compared six devices (Gyenno Spoon, Tremelo, a weighted spoon, S'up Spoon, Steady Spoon, and Eli Spoon) and a regular "control" spoon using an objective eating test. We measured the percentage of successfully transferred couscous to a cup adjacent to the subject's mouth and recorded relative patient preferences. The mean percentages of successful transfer, in descending order of success, were as follows: S'up Spoon (93.6%), Gyenno Spoon (88.9%), weighted spoon (80.7%), Tremelo (78.0%), Steady Spoon (78.9%), control (74.3%), and Eli Spoon (67.6%). Subjective preferences ranked from best to worst based on average ranking were as follows: weighted spoon, S'up Spoon, Gyenno Spoon, Tremelo, control, Steady Spoon, and Eli Spoon. Overall, simple strategies, including a deeper bowl and heavier spoon, outperformed more complicated counterweight/actuator devices.